Porous conducting polymer prepared through liquid crystal template for drug delivery. (2017) - Uppalapati, Dedeepya; Boyd, Ben; Travas-Sejdic, Jadranka; Svirskis, Darren
Unlike conventional controlled drug delivery systems where drug is released at a constant pre-programmed rate, drug release from conducting polymers (CPs) can be controlled through electrical stimuli and adjusted based on the patient's needs. However, owing to their low drug loading capacity and limited electrical responsiveness CP systems cannot currently be applied for systemic drug delivery or to treat chronic disease. To overcome that obstacle one approach is to fabricate porous CP structures. In this work, polypyrrole (PPy) was used owing to its electrical responsiveness and biocompatibility. Liquid crystals were used as a template through which PPy was grown. Dexamethasone phosphate was loaded as a dopant into PPy during polymerisation and its release was quantified by HPLC after the removal of liquid crystal; release could be modified by electrical stimulus. This system has potential applications in conditions where required drug dosing changes with time, such as in age-related macular degeneration.